Further improvements on the phosphotriester synthesis of deoxyribooligonucleotides and the oligonucleotide directed site-specific mutagenesis of E. coli lipoprotein gene. - Hsiung, H (1983)
Two improvements that greatly enhance the rate of phosphotriester oligonucleotide synthesis are described: 1) use of hindered primary amines, e.g. t-butyl amine for decyanoethylation of oligonucleotide triester intermediates, and 2) a simplified isolation procedure that eliminates the tedious bicarbonate extraction after each condensing reaction. Using the improved procedures, oligonucleotide fragments can be synthesized as rapidly as using solid phase chemistry. The final products are purer than those obtained by solid phase chemistry since each intermediate block is purified by chromatography. The technique has been used to synthesize five oligonucleotide fragments (size 15 to 20) for the purpose of performing guided site-specific mutagenesis on a cloned E. coli lipoprotein gene.